The Effect of Money Supply and Bank Indonesia Rate on Consumer Price Index in Indonesia 2018-2022 - Muhammad Ali; Tria Apriliana; Andina Nur Fathonah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
The aim of this research is to determine the influence of the money supply and Bank Indonesia interest rates on the consumer price index in Indonesia for the period 2018 - 2022. The discussion of this research is related to the money supply, Bank Indonesia interest rates, and the consumer price index (CPI). In this regard, the approach taken is theories related to that field. This research was conducted in Indonesia. This type of research is quantitative research. The data used in this research is time series secondary data in the form of publications on the money supply, Bank Indonesia interest rates, and consumer price index from January 2018 to December 2022 obtained from the Central Statistics Agency (BPS) and Bank Indonesia. The research method used in this research is the explanatory method. The data analysis techniques in this research are descriptive analysis and multiple linear regression analysis. The research results show that both partially and simultaneously, there is an influence of the money supply and Bank Indonesia interest rates on the consumer price index.